Urban and industrial symbiosis for circular economy: Total EcoSite integration; Journal of Environmental Management; Vol. 279 - Fan Yee Van; Varbanov P. S. Petar Sabev; Klemesh Zh. Zhiri; Romanenko S. V. Sergey Vladimirovich (2021, 2021)
Title screen